Innovative Nanomaterials for Targeting Hypoxia to Improve Treatment for Triple-negative Breast Cancer - Ray, Suman Kumar; Mukherjee, Sukhes (Recent Patents on Biotechnology, 2024)
Triple-negative breast cancer (TNBC) is an aggressive breast cancer with a high rate of metastases, a short overall survival time, and a poor response to targeted therapy. Improving tumor hypoxia by lowering the oxygen consumption rate of breast tumor cells is a powerful strategy. A viable way to address this issue is to improve therapeutic efficacy by improving the effectiveness of radiation and overcoming drug resistance in TNBC treatment by controlling hypoxia in the tumor microenvironment. The failure of radiation and chemotherapy in TNBC is frequently caused by hypoxia. In TNBC therapy, novel nanomaterials are used for oxygen delivery or generation to affect the tumor microenvironment to improve the effects of ionizing radiation using nanoplatforms. One of the growing fields is novel nano-based drug delivery devices for hypoxic regions and hypoxia- inducible factor-1 (HIF1) targeted therapeutics. Biocompatible nanoparticles may be used in the treatment of TNBC patients in the clinic. Because of the rising market and competition, intellectual property rights (IPR), patents, and tactics may be critically considered. To better comprehend the current state of IPR and patents in cancer nanotechnology, this overview examines recent advances and sophisticated protection measures in this area.
Keywords: clinical outcomes